MUMI BERAROMA MINYAK WANGI, FLUIDITAS IDENTITAS TOKOH PEREMPUAN DALAM RUANG SOSIAL: SEBUAH PENDEKATAN FEMINISME - Imas Uliyah (Faculty of Humanities, Jember University, 2013)
This article is a brief analysis of a novel entitled Mumi Beraroma Minyak Wangi composed by Naning Pranoto (2001). To uncover its content relating to feminism issues, the article looks at first Bourdieu sociology, especially on social space. The subject matter to be dealt with here is focused on social space mobility experienced by the major female character in the story taking the 1965–1997 Indonesia as its background. The basic asumption is that in any social space mobility that occurs, the major female character of the story change her identity as part of the efforts to secure her existence in any environment where she is present. The change in identity forms an expression of concept of identity fluidity, in which one’s identity does not continuously exist in a similar situation. Keywords: feminism, sosial space, identity, fluidity